Pengaruh Kebocoran Data Wajib Pajak Terhadap Kepercayaan dan Kepatuhan Perpajakan Wajib Pajak Orang Pribadi - Purnama, Le Yusfika; Della N., D. Tialurra (LPPM Institut Pendidikan Nusantara Global, 2025)
This study aims to examine the effect of data breaches on trust and tax compliance among individual taxpayers. The sample consists of 113 taxpayer respondents residing in West Nusa Tenggara Province. The sampling technique used is probability sampling with a simple random sampling method based on the Slovin formula. Data were collected through a questionnaire distribution. Data analysis was conducted using SmartPLS version 3.0. The results indicate that data breaches have a significant effect on trust, data breaches have a significant effect on tax compliance, and trust does not have an effect on tax compliance.